Biocompatibility of semiconducting AlGaN/GaN material with living cells - Podolska, Anna; Tham, S.; Hart, Robert; Seeber, R.; Kocan, M.; Kocan, M.; Mishra, U.; Pfleger, K.; Parish, G.; Nener, B. (Elsevier SA, 2012)
With the aim of developing a highly sensitive, mass producible biosensor, we have investigated the growth of human embryonic kidney (HEK) 293 cells on the surface of semiconductor grade AlGaN/GaN heterostructures. Our results demonstrate that, even without specialised surface treatment, a substantial amount of attachment and proliferation of cells is observed. Growth and mortality rates on the AlGaN surface were comparable to standard control culture plates. Quantitative studies of mortality measured by flow cytometry correlate well with qualitative monitoring of biocompatibility. The percentage of dead cells increases marginally with increasing Al concentration. Cell attachment was investigated qualitatively using focused ion beam/scanning electron microscopy (FIB/SEM) and transmission electron microscopy (TEM). Imaging showed strong attachment at the cell/semiconductor interface at the nanometre level. These measurements are the first study of live cell/semiconductor interactions using complementary methods for proliferation, mortality, and attachment, and confirm that the combination of live cells as the biosensing element and AlGaN/GaN heterostructures as the transducer has significant potential for biosensor applications.